Regulation of brown adipocyte metabolism by myostatin/follistatin signaling - Singh, Rajan; Braga, Melissa; Pervin, Shehla (Frontiers in Cell and Developmental Biology, 2014)
Obesity develops from perturbations of cellular bioenergetics, when energy uptake exceeds energy expenditure, and represents a major risk factor for the development of type 2 diabetes, dyslipidemia, cardiovascular disease, cancer, and other conditions. Brown adipose tissue (BAT) has long been known to dissipate energy as heat and contribute to energy expenditure, but its presence and physiological role in adult human physiology has been questioned for years. Recent demonstrations of metabolically active brown fat depots in adult humans have revolutionized current therapeutic approaches for obesity-related diseases. The balance between white adipose tissue (WAT) and BAT affects the systemic energy balance and is widely believed to be the key determinant in the development of obesity and related metabolic diseases. Members of the transforming growth factor-beta (TGF-β) superfamily play an important role in regulating overall energy homeostasis by modulation of brown adipocyte characteristics. Inactivation of TGF-β/Smad3/myostatin (Mst) signaling promotes browning of white adipocytes, increases mitochondrial biogenesis and protects mice from diet-induced obesity, suggesting the need for development of a novel class of TGF-β/Mst antagonists for the treatment of obesity and related metabolic diseases. We recently described an important role of follistatin (Fst), a soluble glycoprotein that is known to bind and antagonize Mst actions, during brown fat differentiation and the regulation of cellular metabolism. Here we highlight various investigations performed using different in vitro and in vivo models to support the contention that targeting TGF-β/Mst signaling enhances brown adipocyte functions and regulates energy balance, reducing insulin resistance, and curbing the development of obesity and diabetes.